Nutrition of healthy infants - Fabian-Danielewska, Anna; Korabiusz, Katarzyna; Wawryków, Agata; Stecko, Monika; Janik-Fuks, Inga; Maciejewska, Martyna; Grudzińska, Ewa; Gibka, Magdalena (Journal of Education, Health and Sport, 2019)
The daily energy requirement of infants depends on age, sex and body weight. Breastfeeding is the most appropriate way to feed babies in the first 6 months of their lives. According to WHO recommendations, one should aim for exclusive breast-feeding for the first 6 months of your child's life. After 6 months, the baby's diet should be extended, continuing breastfeeding. It is recommended to continue feeding with the mother's milk, according to the WHO, until the second year of life, and according to AAP up to 12 months, with the simultaneous introduction of supplementary foods. When, for various reasons, it is not possible to feed the infant with mother's milk, the products substituting for female milk are used. Infant formula is intended for children under 6 months of age and fully satisfies the nutritional needs of an infant. Complementary Feeding should be started between 17 and 26 weeks of age.